2021
DOI: 10.3390/cancers13153842
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mitochondrial DNA Copy Number and Telomere Length with Prevalent and Incident Cancer and Cancer Mortality in Women: A Prospective Swedish Population-Based Study

Abstract: Changes in mitochondrial DNA copy number (mtDNA-CN) and telomere length have, separately, been proposed as risk factors for various cancer types. However, those results are conflicting. Here, mtDNA-CN and relative telomere length were measured in 3225 middle-aged women included in a large population-based prospective cohort. The baseline mtDNA-CN in patients with prevalent breast cancer was significantly higher (12.39 copies/µL) than cancer-free individuals. During an average of 15.2 years of follow-up, 520 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 83 publications
1
17
0
Order By: Relevance
“…However, it is important to note that mtDNA-CN depends on cell-type and the disease in question ( 10 ). For example, using whole blood, we and others have shown that mtDNA-CN is decreased in people with CVDs ( 11 ) whereas both low and high mtDNA-CN have been shown in people with T2D ( 12 , 13 ) and cancer ( 14 ), probably depending on study design, severity of the disease and methods used.…”
Section: Introductionmentioning
confidence: 88%
“…However, it is important to note that mtDNA-CN depends on cell-type and the disease in question ( 10 ). For example, using whole blood, we and others have shown that mtDNA-CN is decreased in people with CVDs ( 11 ) whereas both low and high mtDNA-CN have been shown in people with T2D ( 12 , 13 ) and cancer ( 14 ), probably depending on study design, severity of the disease and methods used.…”
Section: Introductionmentioning
confidence: 88%
“…Li et al 17 conducted a prospective Swedish population-based study and found that mtDNA-CN was inversely associated with allcause and cancer-specific mortality when analyzing all cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported for gastric, kidney, lung, prostate, pancreatic, thyroid, and breast cancers. Several studies demonstrated an association between high mtDNA content and disease severity, 14–25 whereas other studies reported an inverse association 26–28 . A large meta‐analysis conducted by Giaccherini et al 28 revealed significant associations between mtDNA‐CN and specific cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres are repetitive DNA-protein complexes containing TTAGGG repeats, and the length of telomeres shortens accompanying with cell division [ 40 ]. Telomere attrition would affect the mitochondrial function and biogenesis through pathways involving the peroxisome proliferator-activated receptor gamma co-activator 1α/β (PGC-1α/β), p53, and mTORC1 [ 41 , 42 ]. Telomere shortening may activate the DNA damage response (DDR) which in turn causes the increase of mitochondrial content [ 43 ].…”
Section: Discussionmentioning
confidence: 99%